Strengthening the technical capacities of local partners through the use of improved crop seeds in Valle del Cauca: Report - Rendon, Natali; Guerrero, Crhistian (2025)
In September 2025, a technical capacity-building process was carried out in the department of Valle del Cauca, targeting staff from Municipal Agriculture Secretariats and UMATAs, within the framework of the CGIAR Scaling for Impact program, implemented by the Alliance of Bioversity International and CIAT. The initiative aimed to promote the adoption of sustainable agricultural innovations through the use of improved and biofortified maize and bean seeds, thereby contributing to food and nutritional security in rural populations.